2014
DOI: 10.1007/s13318-014-0246-1
|View full text |Cite
|
Sign up to set email alerts
|

Initial dosing regimen of vancomycin to achieve early therapeutic plasma concentration in critically ill patients with MRSA infection based on APACHE II score

Abstract: It is essential to assure the efficacy of antimicrobials at the initial phase of therapy. However, increasing the volume of distribution (Vd) of hydrophilic antimicrobials in critically ill patients leads to reduced antimicrobial concentration in plasma and tissue, which may adversely affect the efficacy of that therapy. The aim of the present study was to establish a theoretical methodology for setting an appropriate level for initial vancomycin therapy in individual patients based on Acute Physiology and Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The vancomycin t 1/2 and V observed in our patients were highly variable and consistent with previously published data . The disparity in t 1/2 and V was not surprising because 30% of the patients had AKI at baseline and 44% had a body mass index ≥30 kg/m 2 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The vancomycin t 1/2 and V observed in our patients were highly variable and consistent with previously published data . The disparity in t 1/2 and V was not surprising because 30% of the patients had AKI at baseline and 44% had a body mass index ≥30 kg/m 2 .…”
Section: Discussionsupporting
confidence: 90%
“…The vancomycin t 1/2 and V observed in our patients were highly variable and consistent with previously published data. 14,22,23 The disparity in t 1/2 and V was not surprising because 30% of the patients had AKI at baseline and 44% had a body mass index ࣙ30 kg/m 2 . We believe these findings limit the utility of dosing nomograms in the ICU setting because they rely on the Cockcroft-Gault equation, which overestimates renal function during the early stages of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the APACHE-II score was not associated with the prognosis of patients with AKI undergoing CRRT. APACHE-II score is one of the most used predictive scoring systems for critically ill patients and has been widely used in predicting prognosis [21][22][23]. However, several studies report conflicting predictive accuracy results associated with the APACHE-II score in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because leakage from capillaries to body cavities increases during inflammation, the volume of distribution of hydrophilic antimicrobials increases in critically ill patients, including patients with sepsis. [16][17][18] In particular, Imaura et al 17 reported that the volume of distribution of VCM was correlated with the Acute Physiology and Chronic Health Evaluation II score, a measure of disease severity associated with inflammatory cytokines, such as tumor necrosis factor-a (TNF-a) and interleukin-6 (IL-6). This is consistent with our finding that CRP is an independent influencing variable.…”
Section: Discussionmentioning
confidence: 99%